Effect of sitagliptin on glucose control in type 2 diabetes mellitus after Roux‐en‐Y gastric bypass surgery. Issue 4 (28th November 2017) - Shah, Ankit; Levesque, Kiarra; Pierini, Esmeralda; Rojas, Betsy; Ahlers, Michael; Stano, Sarah; Holter, Marlena; Dutia, Roxanne; Belsley, Scott; McGinty, James; Laferrère, Blandine
Abstract : The present study was a 4‐week randomized trial to assess the efficacy and safety of sitagliptin, a dipeptidyl‐peptidase‐4 inhibitor, in persistent or recurring type 2 diabetes after Roux‐en‐Y gastric bypass surgery (RYGB). Participants (n = 32) completed a mixed meal test (MMT) and self‐monitoring of plasma glucose (SMPG) before and 4 weeks after randomization to either sitagliptin 100 mg daily or placebo daily. Questionnaires were administered to assess gastrointestinal discomfort. Outcome variables were glucose, active glucagon‐like peptide‐1 and β‐cell function during the MMT, and glucose levels during SMPG. Age (56.3 ± 8.2 years), body mass index (34.4 ± 6.7 kg/m 2 ), glycated haemoglobin (7.21 ± 0.77%), diabetes duration (12.9 ± 10.0 years), years since RYGB (5.6 ± 3.3 years) and β‐cell function did not differ between the placebo and sitagliptin groups at pre‐intervention. Sitagliptin was well tolerated, decreased postprandial glucose levels during the MMT (from 8.31 ± 1.92 mmol/L to 7.67 ± 1.59 mmol/L, P  = 0.03) and mean SMPG levels, but had no effect on β‐cell function. In patients with diabetes and mild hyperglycemia after RYGB, a short course of sitagliptin provided a small but significant glucose‐lowering effect, with no identified improvement in β‐cell function.